Structure Shift in The Indonesian Translation of Pragmatics Textbook Written by George Yule - Mardha Tilla; Havid Ardi (English Language and Literature, 2020)
This study analyzed the structure shift that occurred in English-Indonesian translation. This study employed the descriptive qualitative approach. Data that were found in this research were sentences in the Indonesian translation version of Pragmatics written by George Yule. The textbooks were the source of the data, one as a source language which is English version, another as a target language in Indonesian version. The textbook entitled Pragmatics by George Yule was as a source language, and Its translation which entitle Pragmatik as a target language. The data were collected using document analysis, and data sheet that used to categorize the types of structure shift. There are 70 structure shifts found from the data that were collected and analyzed. There are three types of structure shift. The structure shift of addition appeared 13 times, Omission appeared 21 times, and the structure shift of Head Modifier to Modifier Head in phrase of the sentences in source language and target language appeared 36 times.